2022
DOI: 10.3389/fimmu.2022.801579
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-Mediated Crosstalk Between Keratinocytes and T Cells in Atopic Dermatitis

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by barrier dysfunction, dysregulated immune response, and dysbiosis with increased Staphylococcus aureus colonization. Infiltration of various T helper cell subsets into lesional skin and subsequent cytokine release are a hallmark of AD. Release of cytokines by both T cells and keratinocytes plays a key role in skin inflammation and drives many AD features. This review aims to discuss cytokine-mediated crosstalk between T cells and ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 176 publications
0
16
0
Order By: Relevance
“…It is well known that the transformations that occur in the skin during senescence [ 3 ] and in some diseases, such as dermatoses [ 3 ], may increase the risk of infections that originate due to a virus [ 10 ], bacteria [ 11 ], and fungi [ 12 ]. In the present study, we demonstrated for the first time that hydrolyzed types I and III collagen importantly inhibited the inflammatory response induced by LPS in human fibroblasts (CCD-1072Sk) and human keratinocytes (hKT-nh-skp-KT0026).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the transformations that occur in the skin during senescence [ 3 ] and in some diseases, such as dermatoses [ 3 ], may increase the risk of infections that originate due to a virus [ 10 ], bacteria [ 11 ], and fungi [ 12 ]. In the present study, we demonstrated for the first time that hydrolyzed types I and III collagen importantly inhibited the inflammatory response induced by LPS in human fibroblasts (CCD-1072Sk) and human keratinocytes (hKT-nh-skp-KT0026).…”
Section: Discussionmentioning
confidence: 99%
“…AD and psoriasis are systemic and immune-allergic inflammatory skin diseases, the mechanism of which is the dysregulation of immunology ( 30 32 ), whereas MSCs play a role on regeneration and more importantly on immunomodulation ( 33 35 ). As a result, it could be the new clinical target whether the biological function of MSCs in skin lesion of AD and psoriasis changed and evolved in the pathogenesis of skin inflammatory diseases.…”
Section: The Therapeutic Target Aiming At Lesional Mscs In Ad and Pso...mentioning
confidence: 99%
“…Atopic dermatitis (AD) is a complex disease involving epidermal barrier dysfunction and immunological abnormalities 1 . The communication between keratinocytes and T cells as major drivers of immune dysfunction has been studied extensively 2 . Still, there is data available underlining some contribution of dermal fibroblasts to AD pathogenesis 3 .…”
Section: Figurementioning
confidence: 99%